P863 KEYNOTE-022 parts 4 and 5: pembrolizumab plus trametinib for patients with solid tumors or BRAF wild-type melanoma. (15th April 2020) - Maio, Michele; Carlino, Matteo; Joshua, Anthony; McWhirter, Elaine; Ribas, Antoni; Ascierto, Paolo; Miller, Wilson; Butler, Marcus; Ferrucci, Pier; Zielinski, Robert; Vecchio, Michele Del; Gasal, Eduard; et al.
Abstract : Background: Pembrolizumab+dabrafenib+trametinib demonstrated promising antitumor activity and acceptable tolerability in BRAF-mutant melanoma in phase 1/2 KEYNOTE-022 parts 1 and 2 (NCT02130466 ). Pembrolizumab+dabrafenib+trametinib numerically prolonged PFS and DOR versus placebo+dabrafenib+trametinib but had a higher grade 3-5 TRAE rate in part 3. KEYNOTE-022 parts 4 and 5 evaluated pembrolizumab+trametinib. Methods: In part 4 (open-label, 3+3 dose-finding) patients with advanced solid tumors (irrespective of BRAF status) or unresectable/metastatic BRAF wild-type melanoma received pembrolizumab 200 mg Q3W with trametinib as concurrent (2 or 4 weeks of trametinib run-in [1.5 or 2 mg QD], then pembrolizumab+trametinib [1.5 or 2 mg QD]) or intermittent dosing (2 weeks of trametinib run-in [1.5 or 2 mg QD], then pembrolizumab+trametinib [1.5 or 2 mg QD; 1 week off/2 weeks on]). Interim MTDs identified in part 4 were confirmed in part 5 using a modified toxicity probability interval design. The primary objectives were safety, tolerability, and ORR by investigator assessment per RECIST v1.1 of the maximum administered or tolerated dose (MAD/MTD) of pembrolizumab+trametinib. Safety was analyzed for all patients who received ≥1 dose of study drug; patients treated during the trametinib run-in who discontinued study before receiving pembrolizumab were included; patients who did not complete trametinib run-in or receive ≥66% of planned doses during the 6-week dose-limiting toxicity (DLT) evaluable period were not included for DLT evaluation. AEs were graded per NCI CTCAE v4. Results: Of 42 enrolled patients, most were female (61.9%); median age was 55.0 years; 57.1% had received ≥2 prior lines of therapy. At database cutoff (June 26, 2019), median follow-up was 9.0 months (range, 1.4-25.6 months). Of 38 DLT-evaluable patients, 10 had DLTs (table 1 ). Dosing regimens were selected for confirmation in part 5 based on safety data. Any-grade TRAEs occurred in 39 (92.9%) patients; grade 3-4 TRAEs occurred in 19 (45.2%), none were grade 5. TRAEs led to discontinuation in 8 (19.0%) patients. Immune-mediated AEs occurred in 12 (28.6%) patients, most commonly severe skin reactions (n=6; 14.3%), pneumonitis (n=3; 7.1%), hypothyroidism (n=2; 4.8%). The MTD of concurrent pembrolizumab+trametinib was pembrolizumab 200 mg Q3W plus trametinib 1.5 mg with 2 weeks of trametinib run-in (ORR, 0/16; 0%) and the MTD of intermittent pembrolizumab+trametinib was pembrolizumab 200 mg Q3W plus trametinib 2 mg with 2 weeks of run-in (ORR, 4/15; 26.7%). Conclusions: Both concurrent or intermittent pembrolizumab+trametinib dosing were feasible and the combination showed antitumor activity in patients with advanced solid tumors or advanced BRAF wild-type melanoma.